The Effect Of Strategic Management, Organizational Commitment And Organizational Culture On Employees 'Work Achievement In Higher Education Muhammadiyah Indonesia - Rustamadji Rustamadji; Che Mohd Zulkifli bin Che Omar (Jurnal Pendidikan, 2019)
This study examines the influence of three variables, namely strategic management of organizational commitment and organizational culture to work performance variable, and variable of three variables, namely strategic management of organizational commitment and organizational culture to sesame variable on employee at Muhammadiyah University of Indonesia. The sample used according to the calculation of cluster sampling probability proportionate to size model (PPS) with the formulation of Slovin obtained 386 employees at 12 muhammadiyah universities in Indonesia. The developed instrument combines part of the existing questionnaire related to strategic management, organizational commitment, and work performance, using the Likert Method of Successice Interval (MSI) scale. The use of regression analysis to test the hypothesis can be used if it meets the five underlying classical assumptions, namely normality, multicollinearity, heteroscedasticity, autocorrelation and linearity. Further testing hypothesis in this study using the F test, T test and Coefficient of Determination Test (R2). The results of this study concluded that strategic management of organizational and cultural commitment influences on employee performance, strategic management influence to organizational commitment, organizational commitment influence to strategic organization management culture, organizational commitment and organizational culture, together influence on employee performance.